The Impact of Regional Economic Growth and Factor Input on the Convergence of Health Tourism Industry—Based on the Data of 31 Provinces in China - Qian, Fangbin; Shang, Yunfeng (Frontiers in Environmental Science, 2022)
This study measures the convergence degree of health tourism industry in 31 provinces and autonomous regions of China by input-output method, and investigates the convergence driving force of health tourism industry from five factors: economic growth, talent training, market perfection, technology input and capital investment. The empirical study shows that the level of economic growth, talent training, market perfection, technogy input and capital investment all have a positive effect on the convergence of health tourism industry in China. Moreover, K-cluster analysis is used to divide 31 provinces, municipalities and autonomous regions into three types according to the measured convergence degree, and the five driving forces play different roles in different types of regions with different convergence degrees. For regions where the tourism industry and health industry are well integrated, the two industries can be integrated according to the demand by improving the market system. At the same time, the talent training and technology input can also more effectively promote the convergency of the two industries; For regions where the tourism industry is well integrated with the health industry, strengthening capital investment and talent training can better promote the integration of the two industries; For regions where the health industry is well integrated with the tourism industry, by increasing capital investment, meeting market demand and improving infrastructure investment can the industrial convergency be promoted.